LEARNING PROGRAMMING USING VISUALISATION- AN ANALYSIS OF LEARNER EXPERIENCES - Rehman Ullah, Khan; Fitri Suraya, Mohamad; Yin Bee, Oon; Ahmad Sofian, Shminan; Mohamad Hardyman, Barawi (2021)
Computational thinking and problem-solving are crucial skills of twenty-first-century education. The abstractness and problem-solving nature of programming is a challenge for novice learners. We experimented with an online free visualisation tool called Python Tutor for Object-Oriented C++ programming to improve the learning of visualisation of abstract concepts, problem-solving and computational thinking. In this study, we engaged two classes of undergraduate students. To investigate the learning effects of the visualisation tool in learning, Class One (C1) was treated as an experimental group, and Class Two (C2) was a control group. The same topics were taught to both groups. The experimental group received an opportunity to use the selected tool as they learned the taught content. At the end of two sessions, a quiz was distributed to both groups. Next, C1 was treated as the control group, and C2 became the experimental group. The same topics were thought to both groups. At the end of the two sessions, a second quiz was given to both groups and scores were recorded. To gauge all participants’ problem-solving and computational thinking skills as a whole, we collected data at the beginning and the end of the semester using a Computational Thinking Scales (CTS) and Problem-Solving Test. Findings indicate that the selected visualisation tool helped participants understand and solve ill-defined problems, a critical skill in learning Programming.